Вплив природничо-наукових дисциплін на фахову підготовку бакалаврів психології - Хавіна, Ірина Валер'ївна (Класичний приватний університет, 2017)
У статті розглядаються питання впливу природничо-наукових дисциплін на фахову підготовку бакалаврів психології. Розкрито значення професійної підготовки бакалаврів в галузі "психологія", загальні етапи цієї підготовки. Детально розглядаються дисципліни, які входять до природничо-наукового циклу, та їх вплив на фахову підготовку бакалаврів психології.

The article deals with the influence of natural science disciplines on the professional training of bachelors in the field of psychology. The contribution of the fundamental training of the bachelor in the field of psychology, in contrast to highly specialized education, is considered. The article analyzes the scientific publications devoted to the problem of vocational education, as well as the improvement of the natural-science training of specialists from different directions. The role of natural science training in the professional training of bachelors from psychology is considered.
The influence of natural science disciplines on the professional training of bachelors with psychology
Keywords: конкурентоспроможність; професійна підготовка; природничо-наукова підготовка; освітньо-професійна програма; vocational training